2016
DOI: 10.1111/irv.12398
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of influenza and bacterial coinfection: a systematic review and meta‐analysis

Abstract: AimCoinfecting bacterial pathogens are a major cause of morbidity and mortality in influenza. However, there remains a paucity of literature on the magnitude of coinfection in influenza patients.MethodA systematic search of MeSH, Cochrane Library, Web of Science, SCOPUS, EMBASE, and PubMed was performed. Studies of humans in which all individuals had laboratory confirmed influenza, and all individuals were tested for an array of common bacterial species, met inclusion criteria.ResultsTwenty‐seven studies inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
385
6
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(430 citation statements)
references
References 60 publications
21
385
6
18
Order By: Relevance
“…It is highly probable that the mechanism explaining the higher mortality is due to either to the bacterial infection itself or to an association of virulence factors from both virus and bacteria. Lastly, as shown in this paper and others, the epidemiology of pathogens responsible for co-infection is regional and likely depends on many local factors, but may also be subject to change over time, with emergence in the community of pathogens usually seen in nosocomial infections [6,7,9,12].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…It is highly probable that the mechanism explaining the higher mortality is due to either to the bacterial infection itself or to an association of virulence factors from both virus and bacteria. Lastly, as shown in this paper and others, the epidemiology of pathogens responsible for co-infection is regional and likely depends on many local factors, but may also be subject to change over time, with emergence in the community of pathogens usually seen in nosocomial infections [6,7,9,12].…”
mentioning
confidence: 81%
“…Interestingly, the authors found an apparent increased rate of co-infection over time (from 11.4% in 2009 to 23.4% in 2015), without clear explanation. A recent meta-analysis showed that co-infection rates ranged from 2 to 65% [7]. This difference between studies could be explained by differences in methods of sampling, timing of samples, prehospital antibiotic administration, and different definitions of co-infection (i.e., whether or not it was microbiologically confirmed, etc.).…”
mentioning
confidence: 99%
“…Complications arising from bacterial superinfections have accounted for a significant percentage of influenza‐related morbidity and mortality during pandemic influenza (40%‐95%) and during seasonal influenza (2%‐35%) . Common pathogens responsible for this enhanced disease include the gram‐positive bacteria Streptococcus pneumoniae (pneumococcus) and Staphylococcus aureus .…”
Section: Influenza‐bacteria Coinfection Kineticsmentioning
confidence: 99%
“…Respiratory tract infections are one of the most common acute illness which can be classified into two main types including upper and lower respiratory tract infection (URI, LRI), which caused by bacteria, viruses and mycobacteria . Influenza virus is a major cause of acute respiratory disease in human and many animal species; so that approximately 20% of the world's population annually are infected by influenza, resulting in a significant growth in morbidity and mortality . Influenza, a member of the Orthomyxoviridae family, is characterized by segmented negative‐sense RNA genomes.…”
Section: Introduction and Objectivesmentioning
confidence: 99%